Hungry? Food insecurity, social stigma and embarrassment in the UK - Purdam, K; Garratt, EA; Esmail, A (SAGE Publications, 2015)
In the context of the economic recession and welfare reform in the UK there have been ongoing political debates regarding food insecurity. Food has an important role in defining people’s identities, yet the rapid growth in the number of food banks and food donation points in supermarkets and schools suggests a normalisation of food aid. Moreover, an estimated three million individuals are thought to be at risk of malnutrition in the UK. We examine: the discourse of food aid and the demonisation of those living in poverty, the scale of malnutrition, and the experiences of food bank users by drawing on survey data and case studies. Substantial numbers of people were constrained in their food choices, whilst food bank users had concerns about the social stigma of food aid. It is questionable whether the present policy approach is economically and politically efficient given the impact on people’s health and well-being.